INSTAGRAM SOCIAL MEDIA CONTENT MANAGEMENT IN FAMILY PLANNING COORDINATING BOARD WEST NUSA TENGGARA PROVINCE AS PUBLIC RELATIONS STRATEGIES TO CREATE BRAND AWARENESS - Puala Nesha Setyaningsih; I Wayan Suadnya; Shinta Desiyana Fajarica (JCommsci - Journal Of Media and Communication Science, 2020)
Family Planning Coordinating Board (FPCB) West Nusa Teggara (WNT) Province is a familyplanning and controlling institution. This institution has used Instagram, a social media platform as itschannel to publish its programs and events since 2017. Nowadays, this institution tries to build its ownbrand as an educative intuition for family planning and controlling through Family Planning (KB) andPlanning Generation (GenRe) program. The study sets to describe the WNT FPCB brand awarenessachievement through management social media content activities. Moreover, descriptive qualitative, acase study method has been employed. Purposive sampling Technique has been assigned to select thecorrespondence. Observation, deep interview and document research were utilized to collect the data.The validity and reliability test were done by triangulation and member check. The result showed thataccording to Metrics Framework Public Relations Activity, brand awareness through media social contentmanagement activity have not been met by WNT FPCB.Key Word: Management, Social Media Content, Brand Awareness